2018
DOI: 10.18506/anemon.402461
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Deficiency Payment Supports on the Producer’s Decisions of the Some Cereal Crops in Turkey

Abstract: Bu araştırmada, Türkiye' de hububat grubu içerisinden seçilmiş buğday, arpa ve mısır ekiliş alanları üzerinde fark ödemesi desteklerinin etkileri araştırılmıştır. Araştırmanın değişkenleri ekiliş alanları, cari fiyatların bir gecikmeli değeri ve fark ödemesi destekleridir. Elde edilen sonuçlara göre, arpa ve mısır ekiliş alanları üzerinde fark ödemesi desteklerinin etkili olduğu belirlenmiştir. Buğday' da ise istatistiksel olarak böyle bir etki görülmemiştir. Ancak, cari fiyatlar ile fark ödemesi desteklerinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Işık and Bilgin (2016), who discussed the production effect of market price supports and direct supports, concluded that both of supports increased production level. As a result of the causality analysis of the production effect of agricultural supports applied in Turkey, Yıldız (2017), Doğan et al (2018), Koç and İşlek (2020), and Sağdıç and Çakmak (2021) reached similar conclusions and demonstrated that there is a particularly long-run positive relationship between agricultural supports and production. Some studies on the production effect of agricultural supports applied in Turkey have also focused on livestock supports.…”
Section: Literature Reviewmentioning
confidence: 81%
“…Işık and Bilgin (2016), who discussed the production effect of market price supports and direct supports, concluded that both of supports increased production level. As a result of the causality analysis of the production effect of agricultural supports applied in Turkey, Yıldız (2017), Doğan et al (2018), Koç and İşlek (2020), and Sağdıç and Çakmak (2021) reached similar conclusions and demonstrated that there is a particularly long-run positive relationship between agricultural supports and production. Some studies on the production effect of agricultural supports applied in Turkey have also focused on livestock supports.…”
Section: Literature Reviewmentioning
confidence: 81%